Evaluasi Penyuluhan Pemeliharaan Itik Lokal Jantan Berbasis Metode Inditik Terhadap Tingkat Pengetahuan dan Sikap Petani di Desa Gaum, Kecamatan Tasikmadu, Kabupaten Karanganyar - R Indreswari; A Ratriyanto; R Dewanti (Universitas Sebelas Maret (UNS), 2014)
The aimed of this study was to evaluate the results of extension in local ducks maintenance based on duck and rice intensification method at Farmers Group Sabar Subur Kwarasan, Gaum, Tasikmadu, Karanganyar. The data was collected by using questionnaires. Pretest and posttest data were analyzed by the Wilcoxon test to determine the differences in the level of knowledge and attitudes before and after extension. The results showed that extension quite effective in improving farmers' knowledge in terms of understanding the duckling maintenance management based duck and rice intensification method.Keywords: duck and rice intensification method, maintenance, male local ducks, extension